The Role of Collaborative Learning on Students’ Writing Skills: A Research at English House Language Center - Dhika Pratiwi Arsyad; Sam Hermansyah; Sitti Aisa; Nurul Faradillah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigated the implementation and role of collaborative learning in developing students’ writing skills at English House Language Center. A qualitative case study design was employed to obtain an in-depth understanding of classroom practices and students’ experiences during collaborative writing activities. The participants were six eighth-grade students selected through purposive sampling based on their active involvement and varied writing proficiency. Data were collected through non-participant classroom observation, semi-structured interviews, and documentation of students’ written work. The data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing and verification. The findings revealed that collaborative learning was implemented through small-group discussion, idea sharing, joint sentence and text construction, and peer feedback. These activities encouraged active participation and meaningful interaction throughout the stages of planning, drafting, revising, and editing. Collaboration helped students generate richer ideas, organize texts more systematically, and improve language use, particularly grammar and vocabulary. It also increased motivation, confidence, engagement, and enjoyment, although differences of opinion and unequal participation occasionally required teacher facilitation. The study concludes that collaborative learning is an effective instructional approach for supporting the cognitive, linguistic, affective, and social dimensions of writing development in a non-formal EFL context. Teachers are encouraged to establish clear group roles, provide structured writing tasks, and guide constructive peer feedback.